Irreversibility, Uncertainty, and Cyclical Investment - Bernanke, Ben S. (Quarterly Journal of Economics, 1983)
The optimal timing of real investment is studied under the assumptions that investment is irreversible and that new information about returns is arriving over time. Investment should be undertaken in this case only when the costs of deferring the project exceed the expected value of inforrnation gained by waiting. Uncertainty, because it increases the value of waiting for new information, retards the current rate of investment. The nature of investor's optimal reactions to events whose implications are resolved over time is a possible explanation of the instability of aggregate investment over the business cycle.